Endodontic emergencies: Your medication may be the cause - Verma, Promila (Medknow Publications, 2009)
An endodontic clinician may face unwanted situations during root canal treatment. We present here an unusual case of soft tissue and gingival necrosis of the oral cavity following the use of formocresol(®) during endodontic treatment.